High Pressure Adsorption Isotherm of CO2 on Activated Carbon using Volumetric Method - Martin, Awaludin; Suryawan, Bambang; Alhamid, Muhammad Idrus; Nasruddin, Nasruddin (UI Scholars Hub, 2010)
High Pressure Adsorption Isotherm of CO2 on Activated Carbon using Volumetric Method. Adsorption system is ones of the most effective methods for CO2 separating with other substances that produced from the burning of fossil fuels. In the design for that application, beside of characteristics of porous material (adsorbent) data, CO2 adsorption data on the adsorbent (kinetic and thermodynamic) are also needed. The aim of this research is resulting isothermal adsorption data at pressures up to 3.5 MPa by indirect methods (volumetric method) at isothermal temperature of 300, 308, 318 and 338 K. Adsorbent that used in this research is activated carbon made from East of Kalimantan coals by physical activation method (CO2) which is the surface area of activated carbon is 668 m2/g and pore volume is 0.47 mL/g. Carbon dioxide (CO2) that used in this research is high purity carbon dioxide with a purity of 99.9%. Data from the experiment results then correlated using the Langmuir and Toth equations model. The results showed that the maximum adsorption capacity is 0.314 kg/kg at 300 K and 3384.69 kPa. The results of regression of experiment data using Langmuir and Toth models were 3.4% and 1.7%.